A Invenção da cidade inteligente Rio: uma análise do Centro de Operações Rio pela lente das mobilidades (2010-2016) - Freitas, João Alcantara de (2018)
In April 2010, Rio de Janeiro experienced one of its most recent tragedies: the heavy rains that hit the city and the lack of preparation to deal with emergency situations resulted in the death of more than 300 people. At the same time, the city was preparing to host mega events such as Rio + 20, World Youth Day, the World Cup and the Olympic Games, and a series of multinational companies were seeking to develop partnerships with the City Hall to take advantage of the Rio’s overexposure. With the support of IBM, was inaugurated at the end of 2010 the Rio Operations Center (COR): a control room that monitors all the city's cameras and brings together under one roof representatives from about 30 municipal agencies and security forces. Initially, the COR's goal was to create a protocol for action and shorten the response time for emergencies. Notwithstanding this function, the center became very important in the management of urban mobilities and in preparing the city for mega-events. Although other cities in the world use control rooms to assist urban management, this multi-thematic model was very disruptive and, in a way, qualified Rio de Janeiro as a smart city. The objective of this dissertation is to understand, through the lenses of the New Mobility Paradigm, the invention process (WAGNER, 2010) of Rio de Janeiro as an intelligent city. I treat it as an invention, since, analyzing the evolution of the debate about smart cities over the last decades, I point out that more important than the use of a certain technology has been the narrative that is told from it. The cut of the research is delimited between 2010, when the COR begins to be thought, and 2016, last year of mandate of Eduardo Paes. I propose in this dissertation a multidimensional analysis, recognizing the importance of understanding what COR represents locally and globally. In this sense, the New Mobility Paradigm (SHELLER and URRY, 2016) is fundamental for the development of this research, since it allows a much more comprehensive analysis of complex relational systems of infrastructure and social interaction at multiple scales. In addition, mobilities crosses the present research, as object, at least in three different forms: policies mobilities, urban mobilities and the mobilities of the mega-events. The empirical referential is constructed from eight semi-structured interviews, with: people who worked on the creation or development of COR, including former Mayor Eduardo Paes; an IBM employee who integrated the team that developed the project; an employee of the SEPTA control center (Pennsylvania Southeastern Transit Control Room); and an anthropologist who researches smart cities. Besides the interviews, I was able to make two visits to the COR and one to the SEPTA control center. The research reveals how Rio de Janeiro became "smart" from the development of COR, and how this is fully linked to the context of the mega-events that the city hosted between 2007 and 2016. I also point out how Rio may be foreshadowing a model that in the near future will be spread by other cities.